To live freely in this world : sex worker activism in Africa - Mgbako, Chi (New York : New York University Press, 2016)
Sex worker activists throughout Africa are demanding an end to the criminalisation of sex work and the recognition of their human rights to safe working conditions, health and justice services, and lives free from violence and discrimination. This book tells the story of the brave activists at the beating heart of the sex workers' rights movement in Africa - the newest and most vibrant face of the global sex workers' rights struggle.
Previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 15, 2016).
Keywords: Prostitutes -- Political activity -- Africa; Prostitutes -- Civil rights -- Africa; Prostitutes -- Crimes against -- Africa; Human rights movements -- Africa; Family and Relationships; Crime & criminology; Psychology: sexual behaviour